Presenting a Worthy Governance Model for Tourism in Iran\'s Post-Coronavirus Era - Laaya Jalilian; Mohsen Ahadnejad; hiwa865@gmail.com (تحقیقات کاربردی علوم جغرافیایی)
Policy-making in tourism development planning necessitates the adoption of innovative methodologies within the domain of urban governance. In alignment with this framework, it is imperative to implement policies that focus on the processes of "developing a good governance model for tourism in the post-COVID-19 era in Iran." This approach aims to mitigate the challenges posed by the pandemic, which has imposed significant strain on the tourism industry by reducing the evaluation of tourism governance indicators and establishing a foundation for their implementation. The methodology of this research is descriptive-survey with a practical focus, employing both documentary studies and field research. The qualitative component of the study utilized interviews as a tool for data analysis and the examination of relevant tourism indicators. The statistical population comprises experts and stakeholders involved in the tourism sector in Iran, with a sample size of 14 individuals selected through a combination of purposive and snowball sampling techniques. In-depth semi-structured interviews were conducted, and the data were analyzed through a process of open, axial, and selective coding until theoretical saturation was achieved, leading to the categorization of main and sub-categories. The data analysis was informed by the grounded theory methodology. The findings of this research, which identify indicators of effective governance and elucidate the causal conditions for the application of such governance in Iran's tourism industry, provide a foundation for potential outcomes, including the enhancement of the business environment, particularly in the aftermath of the economic downturn experienced due to the COVID-19 pandemic. These outcomes may lead to the creation of competitive advantages through the establishment of conducive platforms, including organizational measures, infrastructure development, technological enhancements, and the implementation of information and communication management strategies, marketing strategies, and oversight mechanisms, all of which are articulated as a comprehensive model.